2012
DOI: 10.1152/ajpgi.00015.2012
|View full text |Cite
|
Sign up to set email alerts
|

Activated hepatic stellate cells upregulate transcription of ecto-5′-nucleotidase/CD73 via specific SP1 and SMAD promoter elements

Abstract: sine is a potent modulator of liver fibrosis and inflammation. Adenosine has been shown to regulate such diverse activities as chemotaxis, contraction, and matrix production in hepatic stellate cells (HSC). Ecto-5=-nucleotidase/CD73 [EC 3.1.3.5] is the rate-limiting enzyme in adenosine production. Cd73-deficient mice are resistant to experimental liver fibrosis and have impaired adenosine generation. However, cell-specific expression and regulation of CD73 within the fibrotic liver have not been defined. In pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 48 publications
1
44
0
Order By: Relevance
“…NTPDase8 has been identified as a hepatocyte canalicular marker [57]; however, expression was detected in HSC and Mz-ChA-1 cells as well. In contrast, CD73 is expressed in hepatocytes in normal liver; however, expression is dramatically redistributed to HSC [58] in the cirrhotic liver. Thus, there may be a disconnection between mRNA expression and protein expression in the cell lines we have examined.…”
Section: Ecto-nucleotidasesmentioning
confidence: 87%
“…NTPDase8 has been identified as a hepatocyte canalicular marker [57]; however, expression was detected in HSC and Mz-ChA-1 cells as well. In contrast, CD73 is expressed in hepatocytes in normal liver; however, expression is dramatically redistributed to HSC [58] in the cirrhotic liver. Thus, there may be a disconnection between mRNA expression and protein expression in the cell lines we have examined.…”
Section: Ecto-nucleotidasesmentioning
confidence: 87%
“…We have previously cloned and characterized the rat Nt5e promoter and shown that Nt5e gene expression is transcriptionally regulated in activated liver myofibroblasts during fibrosis in the rat species [15]. Here, we use a similar approach to identify Nt5e gene promoter in the mouse species and study the regulation of its transcriptional activity in activated mouse liver myofibroblasts.…”
Section: Resultsmentioning
confidence: 99%
“…In the healthy liver, Cd73 expression is mostly found in parenchyma, endothelium, and both quiescent hepatic stellate cells, and portal cells [14]. In the fibrosing liver, it is redistributed to, and transcriptionally regulated, the liver MF deriving from activated HSC and PF of murine and human origins [15][16][17][18]. For instance, Sp1/Smad transcription factors regulate Cd73 gene expression in rat HSC-derived liver MF [15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ecto-5′-nucleotidase (CD73) activity was found to be higher in the quiescent, rather than in the activated phenotype of a HSC line, suggesting that ecto-5′-nucleotidase-dependent adenosine production may play a role in the regulation of quiescent HSC functions [6]. However, it has been claimed recently that ecto-5′-nucleotidase (CD73) gene expression increased in both HSC and portal fibroblasts during myofibroblastic differentiation and represents a promising target for antifibrotic therapy [85].…”
Section: Fibrosis and Hscsmentioning
confidence: 99%